2013
DOI: 10.1007/s00508-013-0456-6
|View full text |Cite|
|
Sign up to set email alerts
|

Epidemiology of traumatic brain injury in Austria

Abstract: SummaryBackgroundTraumatic brain injury (TBI) is an important cause of preventable deaths. The goal of this study was to provide data on epidemiology of TBI in Austria.MethodsData on all hospital discharges, outpatients, and extra- as well as in-hospital deaths due to TBI were collected from various sources for the years 2009–2011. Population data (number of male/female people per age-group, population of Austrian cities, towns, and villages) for 2009–2011 were collected from the national statistical office. I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
31
2
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 50 publications
(40 citation statements)
references
References 20 publications
4
31
2
3
Order By: Relevance
“…Moreover, alcohol and older age predicts fatal outcome . The mortality (defined as GOS 1) in our study was 18.2% but Brazinova et al report a wide range of mortality rates in their systematic review on TBI in Europe; from 9/100.000/year to 28/100.000/year in national level studies like ours, but those numbers include all TBI, not only TBI admitted to the ICU . Raj et al report data on all moderate and severe TBI from a nationwide Finnish ICU multi‐center database.…”
Section: Discussionmentioning
confidence: 50%
“…Moreover, alcohol and older age predicts fatal outcome . The mortality (defined as GOS 1) in our study was 18.2% but Brazinova et al report a wide range of mortality rates in their systematic review on TBI in Europe; from 9/100.000/year to 28/100.000/year in national level studies like ours, but those numbers include all TBI, not only TBI admitted to the ICU . Raj et al report data on all moderate and severe TBI from a nationwide Finnish ICU multi‐center database.…”
Section: Discussionmentioning
confidence: 50%
“…For the breakdown of rate ratios by separate years please see Supplementary Eur Spine J attributed to increasing life expectancy and thus larger population at risk and in Austria is apparent also in the case of traumatic brain injuries [25,26].…”
Section: Discussionmentioning
confidence: 98%
“…In studies of all ages, all TBI severities, and all mechanisms, the lowest reported mean age was 26.7 in the Republic of San Marino (Servadei and colleagues [1985]), 28 the highest was 44.5 in Austria in 2009-2011. 32 The reported proportion of males was always greater than that of females (irrespective of age, severity and mechanism of injury), ranging from 55% in Sweden in 2001 34 to 80% in Ireland in 2005-2007. 35 …”
Section: Age and Sexmentioning
confidence: 99%